Compulsory Licensing in Intellectual Property Rights (IPR): Current Application and Future Prospects in Indonesia - Sahlan, Sahlan; Nurman, Ilham; Uddin, Abdul Karim; Daeng Kunu, Andi Bustamin (Universitas Lampung, 2024)
The implementation of Compulsory Licensing in the procurement of anti-retroviral drugs to combat the HIV/AIDS epidemic, which poses a significant threat to Indonesia and global public health, exemplifies the essential necessity and utility of this concept. Compulsory Licensing is pivotal not only for community health but also for advancing Intellectual Property Rights (IPR) law. This research aims to explore the future prospects of Compulsory Licensing and propose regulatory reforms in Indonesia. Utilizing a normative juridical approach, the study concludes that Compulsory Licensing holds strong potential as a countermeasure and in balancing rights and obligations. It underscores the critical need for a robust regulatory framework to support its effective application and growth. Future enhancements, such as allowing appeals against government compensation determinations through judicial review, could bolster acceptance and ensure the sustainability of this concept.